Does the implementation of evidence-based and culturally competent practices reduce disparities in addiction treatment outcomes?. (October 2017) - Guerrero, Erick G.; Garner, Bryan R.; Cook, Benjamin; Kong, Yinfei
Abstract: Rationale: Research is limited on the extent to which implementation of evidence-based and culturally responsive practices reduces outcome disparities in substance use disorder treatment. We examined the role of contingency management treatment (CMT), medication-assisted treatment (MAT), and culturally competent practices on Mexican Americans' rate of successful completion of treatment. Methods: We analyzed a concatenated dataset from 153 publicly funded substance use disorder treatment programs in Los Angeles County, California, in 2011 and 2013. These data were merged with data from 15, 412 adult clients in both periods, of whom we selected only Mexican Americans (46.3%) and non-Latino Whites (53.7%). The outcome was successful treatment completion. The main independent variables were client demographics, drug use severity, mental health issues, and program license and professional accreditation. Results: Less than half of the programs highly implemented CMT, MAT, and culturally competent practices. CMT and cultural competence were not associated with successful treatment completion. However, Mexican Americans in programs with high degree of implementation of MAT had higher odds of successfully completing treatment compared to non-Latino Whites and programs with low MAT ( OR  = 1.389; 95% CI = 1.018, 1.897). Conclusions: Findings highlight the role of MAT in reducing the disparity in treatment completion between Mexican Americans and non-Latino Whites. Implications for health policy and the dissemination of MAT are discussed. Highlights: Examined the role of contingency management (CMT), medication assisted treatment (MAT) and cultural competence in treatment completion. Less than half of the programs had highly implemented CMT, MAT and culturally competent practices. Mexican Americans in programs with high implementation of MAT had higher odds of completion compared to Whites and low implementation programs.